Pemikiran Abdullah Ahmed An-Naim tentang Dekontruksi Syari’ah sebagai Sebuah Solusi - Ahmad Taufiq (Universitas Islam Negeri (UIN) Walisongo Semarang, Indonesia, 2018)
The laws contained in the Qur'an still exist that require interpretation and have the potential to develop. Muslims worldwide may be entitled to apply Islamic law, provided it does not violate the rights of other people and groups, both within and outside of the Islamic community. That is, in claiming and using individual and collective rights to self-determination, Muslims must also recognize and guarantee equal rights for others. Abdullah, descriptive-analytical nature. Ahmed An-Naim to answer the gap between shari'ah and issues of modernity . Shari'a decontructions are used for Islamic legal issues using the Knife of Analysis used first by Mahmud Thaha's Theory of Law Evolution, the second nasikh mansukh theory, the third Makiyyah and Madaniyah, the fourth the interpretation of the gender-based text, the fifth concept of shari'a on human rights